Flat, cheap, and under control [electrochemical mechanical planarization]. - Brown, A.S (IEEE spectrum)
This paper describes Applied Material's wafer polishing technology, called electrochemical mechanical planarization (ECMP). ECMP is the answer to the problems of electropolishing and chemical mechanical planarization (CMP) of the chip-making process: manufacturing faster, more powerful chips without obliterating their vanishing fine and increasingly fragile features. It is designed to remove excess copper from the top of a newly formed layer of wiring on a chip without damaging the fragile insulation material, called a dielectric, beneath it. ECMP combines aspects of two other technologies, chemical mechanical planarization (CMP) and electropolishing.